2012
DOI: 10.54865/mjas1221089k
|View full text |Cite
|
Sign up to set email alerts
|

ECONOMICAL BENEFIT FROM OSTRICH (Struthio camelus L.) BREEDING AND PRIMARY PROCESSING

Abstract: This work includes the economic benefit of ostrich rising and methods of primary analyses, ostrich transport to the slaughter house resting before primary treatment, stunning with blood, plucking the plumage, cutting the legs and the head, exenteration (removal of internal organs), washing, filtration and cooling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Generally found in arid countries, ostriches sustain themselves on a diet of fruits, juicy plants, and tiny insects [1]. Currently, there are more than 5,000 ostrich farms worldwide, including those in Australia, Argentina, Botswana, Brazil, France, Israel, Namibia, Spain, England, the United States of America, and Thailand [2]. All parts of ostriches find extensive use in various products, such as clothing, gloves, shoes, and handbags.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally found in arid countries, ostriches sustain themselves on a diet of fruits, juicy plants, and tiny insects [1]. Currently, there are more than 5,000 ostrich farms worldwide, including those in Australia, Argentina, Botswana, Brazil, France, Israel, Namibia, Spain, England, the United States of America, and Thailand [2]. All parts of ostriches find extensive use in various products, such as clothing, gloves, shoes, and handbags.…”
Section: Introductionmentioning
confidence: 99%
“…Omega-9 fatty acids, including oleic acid, offer numerous health benefits, such as promoting heart health, maintaining balanced cholesterol levels, enhancing immune function, and improving skin health [14,17,20]. Several studies have demonstrated that ostrich oil, comprising omega-3, omega-6, and omega-9 fatty acids, exhibits potential in reducing nerve pain, suppressing inflammation, treating conditions like rheumatoid arthritis and asthma, lowering blood pressure, decreasing the risk of heart disease, and protecting aging skin [2,6,14,15,17,19].…”
Section: Introductionmentioning
confidence: 99%